2020
DOI: 10.1093/schbul/sbaa069
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Probabilistic Prediction and Bayesian Learning Can Explain Reduced Neural Semantic Priming in Schizophrenia

Abstract: It has been proposed that abnormalities in probabilistic prediction and dynamic belief updating explain the multiple features of schizophrenia. Here, we used electroencephalography (EEG) to ask whether these abnormalities can account for the well-established reduction in semantic priming observed in schizophrenia under nonautomatic conditions. We isolated predictive contributions to the neural semantic priming effect by manipulating the prime’s predictive validity and minimizing retroactive semantic matching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…In patients diagnosed with schizophrenia, recent data showed that they are less able to mobilize predictive mechanisms to facilitate processing at the earliest stages of accessing the meanings of incoming words. 63 …”
Section: Discussionmentioning
confidence: 99%
“…In patients diagnosed with schizophrenia, recent data showed that they are less able to mobilize predictive mechanisms to facilitate processing at the earliest stages of accessing the meanings of incoming words. 63 …”
Section: Discussionmentioning
confidence: 99%
“…Word-level semantic processing in schizophrenia is most commonly investigated via priming paradigms. Yet, the literature is inconsistent in terms of whether the priming-N400 effects are enhanced or reduced in patients (Mathalon et al, 2002(Mathalon et al, , 2010Salisbury, 2008;Sharpe et al, 2020). This discrepancy may result from impairments at different levels of the linguistic hierarchy.…”
Section: Semantics: Impaired Predictive Coding In the Beta-and Gamma-mentioning
confidence: 99%
“…This discrepancy may result from impairments at different levels of the linguistic hierarchy. Patients may be impaired in lexical access (Kuperberg et al, 2019), may suffer from reduced or enhanced semantic activation (Titone et al, 2000;Mathalon et al, 2010), or may fail to derive predictions from the word context (Sharpe et al, 2020). Of note, the prediction failure account accords with results from sentence-level N400 studies: Whereas the N400 reflecting semantic retrieval and integration seems to be unaffected in schizophrenia (Kuperberg et al, 2006), converging evidence has shown that patients are unable to utilize contextual information to suppress irrelevant meanings of a target word, for example, when comprehending a homophone (Sitnikova et al, 2002).…”
Section: Semantics: Impaired Predictive Coding In the Beta-and Gamma-mentioning
confidence: 99%
“…This suggests that PSZ have difficulty updating their beliefs even in the face of disconfirmatory evidence compared to healthy control subjects (HCS) [15]. In addition to the perceptual level [15,16], similar deficits have also been observed at the level of higher-order processes that involve evidence gathering [17][18][19], probability learning [20][21][22], and language processing [23,24]. It is also worth noting that this deficit in prediction updating was found to be associated with the severity of delusional symptoms in PSZ, indicating the potential interplay between belief updating and delusion development in schizophrenia [15].…”
Section: Introductionmentioning
confidence: 97%